Why Do Japanese People Use Masks Against COVID-19, Even Though Masks Are Unlikely to Offer Protection From Infection? - Nakayachi, Kazuya; Ozaki, Taku; Shibata, Yukihide; Yokoi, Ryosuke (Frontiers in Psychology, 2020)
Wearing masks against COVID-19 is beneficial in suppressing pandemic spread, not through preventing the wearer from being infected but by preventing the wearer from infecting others. Despite not providing much protection, the custom of wearing masks has prevailed in East Asia from the early stages of the pandemic, especially in Japan, to such an extent that it caused a shortfall in supply. Why do many Japanese people wear masks during the COVID-19 pandemic, even though masks are unlikely to prevent them from getting infected? We examined six possible psychological reasons for wearing masks: three involved expectations about the risk of infection, and three involved other driving psychological forces. The results of our nationwide survey revealed that people conformed to societal norms in wearing masks and felt relief from anxiety when wearing masks. However, risk reduction expectations did not affect mask usage. The social psychological motivations successfully explained much about mask usage. Our findings suggest that policymakers responsible for public health should consider social motivations when implementing public strategies to combat the COVID-19 pandemic.